Penggunaan Media Realita Untuk Meningkatkan Kemampuan Belajar Matematika Konsep Bangun Ruang - Sukadi (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
Reality media is all real media which is available in nature environment, as well using whilealive or in the preserved condition. Reality media is a real thing which is using as a material orlearning resource. Based on the research result which is done in two cycles, it can be concludethat reality media is able to increasing the math learning ability in geometry concept in thestudent of fourth grade SD N Rejosari 01 in the academic year 2014/2015. The increasing ofstudent learning ability in math subject in the geometry concept is proved by the appearingof student score in each cycle. In the pre-cycle, the average score of student learning result inmath subject in geometry concept is 55,0, then it the first cycle, the student average scoreincrease to be 66,5, and in the second cycle, the average ability score also increase into 77,0